PENINGKATAN KETERAMPILAN MENDENGARKAN DENGAN PEMBELAJARAN TIPE JIGSAW SISWA KELAS XI IPA 1 SMA NEGERI 1 PLERET BANTUL TAHUN AJARAN 2012/2013 - Ermawati Ermawati; Siti Rochmiyati (CARAKA, 2015)
The purpose of this research is to describe the result of the students listening short story ability and to describe the student's activities by usingÂ  Jigsaw learning Method. This research belongs to Class Action Research. The Subject of this study are the science students 1 grade XI of State Senior High School 1 of Pleret Bantul in academic year 2012/2013 and there are the amount of 29 students. This research is conducted in two actions cycle. In this research, the writer used instruments to measure the learning goal of students listening abilities are quiz and observation worksheet to describe the students learning activity. The result of this research shows that (1) Jigsaw type can improve the students listening ability. The improvement of the student's ability in listening short story can be seen from the short story identification understanding and KKM achievement outcome in each cycle. Understanding of short story identification in theme increase 7%, from 75% in cycle I become 82% in cycle II. Understanding of characters identification increase 14%, from 79% in cycle I become 93% in cycle II. Understanding of plot identification increase 14%, from 68% in cycle I become 82% in cycle II. Understanding of setting identification increase 5%, from 85% in cycle I become 90% in cycle II. The result of KKM achievement can be seen by the improvement of student success in listening a short story. KKM achievement in 18 students (62%) who succeed in precycle, increase 3 students (10%) become 21 students (72%) who succeed in the cycle I and increase 8 students (25%) become 29 students (100%) get succeed in cycle II. Jigsaw type can increase the student learning activity. Percentage average of the student's activity increases 20% from 41% in precycling become 61% in cycle I and increase 25% become 86% in cycle II.